Frequency of stroke patients qualified for recombinant tissue plasminogen activator (r-TPA) injection and limitations in Zahedan 2016 - Khosravi, Alireza; Farzadfard, Mohammad-Taghi; Abdollahpour, Arezoo (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Stroke is one of the common causes of mortality and disability. By introducing r-TPA into the global drug market and its effect on the patients’ prognosis, using this drug is recommended in all patients with ischemic stroke who visited less than 4.5 hours after stroke and do not have contraindications. The aim of this study was to investigate the frequency of stroke patients qualified for recombinant tissue plasminogen activator (r-TPA) and its limtations. Methods: In this descriptive cross-sectional study, 244 patients examined with stroke admitted to the Neurology Department of Zahedan city hospital in 2016. Information form were completed with demographic data, transmission method, referral time, CT scan preparation time, and the response of the patients’ trials, and finally the data were inserted in SPSS.16 software and analysed by statistical methods. Results: Out of all patients with ischemic stroke, 28 (11.5%) patients had contraindication to receive drug. Of 216 remain patients, 201 patients (93.1%) had no possibility to receive r-TPA due to the loss of golden time and only 15 patients (6.9%) had possibility to receive drug because of visited 4.5 hours before the beginning of symptoms. Of them, 3 (20%) patients due to delay in CT scan and test results, had no possibility to receive r-TPA. In summary, of all patients with inclusion criteria, only 12 (5.5%) patients could use the r-TPA in this study. Conclusions: The most important barrier to using r-TPA has been the loss of golden time and training to raise awareness of the society can lead to early referral from the onset of stroke symptoms.